Analysis of risk factors of postoperative mortality in peritoneal dialysis patients with developed peritonitis - Erkent, Murathan; Karakaya, Emre; Avci, Tevfik; Bagci, Zeynep Ilayda; Akdur, Aydincan (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. Peritoneal dialysis (PD)-associated peritonitis can lead to dysfunction in PD delivery as a result of thickening of the peritoneal membrane, usually due to recurrent peritonitis, and result in peritonitis with ileus or intestinal perforation. This study sought to investigate the risk factors that lead to mortality in patients receiving PD who underwent surgery for peritonitis. Methods. The study was designed as a retrospective observational study and included 36 patients who received PD and underwent surgical treatment for peritonitis between 2011 and 2020. Data on patient demographics, comorbid diseases, duration of PD application, number of peritonitis episodes due to PD, surgical procedures performed due to peritonitis, and postsurgical morbidity and mortality rates were collected. Results. It was found that mortality increased with advancing age in patients with coronary artery disease (CAD) compared to those without CAD, and this increase was statistically significant (p = 0.002). In addition, it was determined that the accompanying cirrhosis significantly increased mortality in elderly patients (p = 0.043). In considering the surgical procedures performed, it was found that segmental small-bowel resection (n = 16) was mostly performed due to ileus or intestinal perforation, and no additional pathological findings other than peritonitis were encountered in 12 patients. Mortality occurred in eight patients in the advanced-age group and one patient in the other group among patients operated on for peritonitis. No difference in mortality rate was found according to the surgical procedure (p = 0.512). Binary logistic regression analysis was applied and age, coroner artery diseases (CAD), and dialysis time for risk of mortality. Respectively, age (odds ratio [OR]= 1.09; 95% Cl [1.013-1.193]; p=0.024), CAD [OR] = 43.7; 95% Cl [5.191-368.755]; p <.001 and dialysis time [OR] = 1.786; 95% [1.060-3.010]; p=0.029 was calculated. Conclusions. Mortality increased by 1.09 times for each one-year increase in age after 52.5 years of age and also CAD increased the mortality rate by 43.7 times. Prolonged PD duration increased the mortality rate especially after 11.5 months, increased the peritonitis-related mortality rate by 1.7 times. We propose that since surgical interventions may be performed in peritonitis due to PD; and do not increase peritonitis-related mortality, an appropriate surgical procedure can be performed safely in experienced centers before it is too late.